1971
DOI: 10.1161/01.str.2.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Alpha and Beta Adrenergic Receptors in Canine Cerebral Vasculature

Abstract: The cerebral vascular effects of various adrenomimetic agents were examined in 12 isolated canine brains perfused with blood at constant flow. Changes in cerebral vascular resistance (CVR) and the magnitude of pressor or depressor responses observed following drug injection were examined. The presence of alpha adrenergic receptors in this vascular bed is indicated by the increased CVR observed when phenylephrine, norepinephrine, and epinephrine were administered and by the reduced or reversed pressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 21 publications
4
18
0
Order By: Relevance
“…1 ' 2 In accordance with the findings of other authors, 3 ' 6 our earlier studies 7 revealed a weak alpha-adrenergic and betaadrenergic activity of the cerebral vessels of the isolated perfused dog brain. Since these investigations were obtained with injections of catecholamines, no conclusion could be made whether the vasoconstrictor response of cerebral vessels to norepinephrine or the Supported by a Grant of the Deutsche Forschungsgemeinschafl.…”
Section: Additional Abstract Epinephrine Cerebral Metabolism Cerebrasupporting
confidence: 86%
“…1 ' 2 In accordance with the findings of other authors, 3 ' 6 our earlier studies 7 revealed a weak alpha-adrenergic and betaadrenergic activity of the cerebral vessels of the isolated perfused dog brain. Since these investigations were obtained with injections of catecholamines, no conclusion could be made whether the vasoconstrictor response of cerebral vessels to norepinephrine or the Supported by a Grant of the Deutsche Forschungsgemeinschafl.…”
Section: Additional Abstract Epinephrine Cerebral Metabolism Cerebrasupporting
confidence: 86%
“…These results are consistent with experiments in the isolated circulation of the dog 4 and in isolated cerebral arteries of the cat. 17 In summary, with this experimental technique we have demonstrated that norepinephrine and epinephrine produce marked cerebral vasoconstriction by their direct action and isoproterenol produces vasodilation, also by a direct action.…”
Section: Discussionsupporting
confidence: 91%
“…4 The decrease in cerebral blood flow induced by epinephrine and norepinephrine was blocked to a significant extent after local administration of phenoxybenzamine, suggesting the presence of alpha adrenergic receptors in the brain vasculature, which is in agreement with experiments carried out on the isolated cerebral circulation of the dog. 4 The effects of epinephrine and norepinephrine, however, were not reversed after administration of phenoxybenzamine, probably because of the relatively small dose of blocking agent used. 13 Although agreement exists that intravenously administered isoproterenol increases cerebral blood flow, the mechanism responsible remains obscure.…”
Section: Discussionsupporting
confidence: 86%
“…20 Edvinsson and Owman" have demonstrated blockade of isoproterenol-induced constrictions of cerebral arteries in vitro by propranolol and cited this as further evidence for the presence of beta-receptors. In contrast, Rosenblum 22 and Kuschinsky and Wahl 28 could not show significant alterations in pial arterial diameter by either isoproterenol or propranolol.…”
mentioning
confidence: 99%